Using Hierarchical Clustering and Summarisation Approaches for Web Retrieval: Glasgow at the TREC 2002 Interactive Track - Osdin, Richard; Ounis, Iadh; White, Ryen W. (Text REtrieval Conference - 11 (TREC 2002) Gaithersburg, Maryland, U.S.A., 2002)
Current search engines are typified as having a lack of precision, coupled with an elongated ranked list style of result presentation. When combined, these factors make relevant data extraction increasingly complex. The main investigation of our participation in the Interactive Track of TREC 2002 is to assess the effectiveness of new visualisation techniques for displaying the results of search engines. Our current system, provisionally named HuddleSearch, uses a newly developed clustering algorithm, which dynamically organises the relevant documents into a traversable hierarchy of general to more-specific cluster categories. We have extended our TREC-10 summarisation tool to also allow the summarisation of multiple documents; whereby a summary paints a caricature of the contents of a cluster, rather than an individual document, thus allowing the user to provisionally judge a cluster’s relevance prior to viewing its contents. The interaction between the user and the system is further developed by the aid of an information visualisation tool. Our primary assumption is that the combination of both hierarchical clustering and summarisation tools will aid users in their interaction with the system in the Web context.